Variation in perfluoroalkyl acids in the American alligator (Alligator mississippiensis) at Merritt Island National Wildlife Refuge - Bangma, Jacqueline T. (Chemosphere, 2016)
This study aimed to quantify concentrations of fifteen perfluoroalkyl acids (PFAAs) in the plasma of American alligators (Alligator mississippiensis) inhabiting wetlands surrounding the Kennedy Space Center (KSC) in Florida, USA located at Merritt Island National Wildlife Refuge (MINWR). Approximately 10 male and 10 female alligators (n(total) = 229) were sampled each month during 2008 and 2009 to determine if seasonal or spatial trends existed with PFAA burden. PFOS represented the highest plasma burden (median 185 ng/g) and PFHxS the second highest (median 7.96 ng/g). While no significant seasonal trends were observed, unique spatial trends emerged. Many of the measured PFAAs co-varied strongly together and similar trends were observed for PFOS, PFDA, PFUnA, and PFDoA, as well as for PFOA, PFHxS, PFNA, PFTriA, and PFTA, suggesting more than one source of PFAAs at MINWR. Higher concentrations of PFOS and the PFAAs that co-varied with PFOS were collected from animals around sites that included the Shuttle Landing Facility (SLF) fire house and the Neil Armstrong Operations and Checkout (O&C) retention pond, while higher concentrations of PFOA and the PFAA that co-varied with PFOA were sampled from animals near the gun range and the old fire training facility. Sex-based differences and snout-vent length (SVL) correlations with PFAA burden were also investigated.